The emotional geographies of belonging: children's intersectional identities in primary school. Issue 1 (2nd January 2017) - Kustatscher, Marlies
Abstract : This article examines the role of emotions for young children's social identities of ethnicity, race, nationality, class, gender and culture in the context of a Scottish primary school. It argues that emotions contribute to how intersectional identities are performed in children's peer relationships within the discourses available to them, and that analysing emotions is crucial for understanding how children's intersectional belongings come to be constructed and politicised. This makes emotions a highly political matter, important for understanding the complexity of intersectionality and for informing childhood policy and practice.